Single or Divided Administration of Cisplatin Can Induce Inflammation and Oxidative Stress in Male Sprague-Dawley Rats - Brigitte Rina Aninda Sidharta; Bambang Purwanto; Brian Wasita; Vitri Widyaningsih; Soetrisno Soetrisno (Indonesian Biomedical Journal, 2022)
BACKGROUND: Cisplatin is one of the most potent chemotherapy drugs to treat various types of cancer, however the use of cisplatin has some the adverse effect, such as the increase of oxidative stress and inflammation by malondialdehyde (MDA) and nuclear factor kappa B (NF-kB) activation. Since the dosing of cisplatin is critical, we observed the effect of single and multiple doses of cisplatin injection on rats’ inflammation and oxidative stress level.